Characterization of baculovirus isolated from Spodoptera litura larvae - Ch'ng, Serena Chooi Ling. (2014)
Baculoviruses are host specific towards arthropods and incapable of infecting mammals and plants. Insects infected with baculovirus can be distinguished through behavioural differences and the symptoms occur in the insects as compared with the healthy insect. Several symptoms like changes in the integument colour, cease feeding, regurgitation and liquefy larval body content will occur in insects infected with baculovirus. During insect rearing of Spodoptera litura, some larvae had show symptoms associated with virus infections such as loss in appetite, changes in integument colour and liquefied body after death. Further identification had confirmed the presence of polyhedral-shaped occlusion body (OB) inside the diseased larvae. The OBs were measured about 1.74 to 2.26 μm in diameter. There were two distinct batches of diseased larvae with either pinkish or whitish integument seen during propagation of the virus. Molecular identification using polihedrin gene has confirmed that the causal agent was SpltNPV.
Project paper (B.Hort.Sc.) - Universiti Putra Malaysia, 2014.